Board gender diversity and financial stability: Evidence from microfinance institutions - Thuy T. Dang; Trang Nt Ho; Duc Nguyen Nguyen (Cogent Economics & Finance, 2023)
The effects of board gender diversity (BGD) on financial stability of financial institutions have long been an important topic, creating a rich strand of literature that focuses extensively on banks. Meanwhile, little is known about the implications of BGD on risk in microfinance institutions (MFI). This study aims to fill this gap. Using a data sample retrieved from the MIX Market database spanning the 2009-2018 period and the random-effects estimator, we find that the proportion of female directors on the board is positively associated with financial stability of MFIs measured by the Z-score. The result is robust when using alternative measures of financial stability and BGD, and alternative estimation techniques. In addition, we document a negative relationship between BGD and risk-taking behavior of MFIs. Further, the research result favors the critical mass theory rather than tokenism. Lastly, we find that BGD links with financial stability in a monotonic instead of non-monotonic manner.
Keywords: G21; G32; G34; M14; 330; female directors; financial stability; gender diversity; microfinance institutions; risk